The history of the origin of the affixes of the recent past (Eurasian Journal of Philology Science and Education, 2018)
Forms of past tense -dy,di,ty,ti (-ды (-ді, -ты, -ті) are used in Turkic languages. There is nothing that attracts attention in semantics. Well known scientists wereThis suffix attracted well known scientists attention. For example, O.Betling wrote that it appeared from historical development of -dyk (–дық) action pronoun. S.E. Malov supposed that it could have appeared from the –dy of adverbial participle formant. Though these forms don’t have formal resemblance they are not considered as past tense. Authors tried to prove in the aricle that past tense forms apperared from the auxiliary verb (арты>ерті) arty>erty. It was developed in two directions: when syllables ar~er (ар~ер) are deleted -ty, ti (-ты/-ті) come into usage, while sonar r (р) is omitted in arty>erti (арты>ерті) auxiliary verb e+di (е+ді) appeared.